PENGARUH APLIKASI COMICA TERHADAP MINAT MENULIS CERITA PADA SISWA KELAS V SD 111/1 MUARA BULIAN - Ema Methalia; Irma Suryani; Andi Gusmaulia Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Writing is the key to clarifying thoughts and ideas, expressing and clarifying oneself, and improving critical thinking skills, and is a source of self-evaluation. Writing is also a very important part of life literacy. Literacy management is becoming increasingly necessary in today's era. Minister of Education and Culture Nadiem Makarim said that literacy fosters critical thinking and ethical use of digital platforms, especially among the younger generation. However, elementary school students' interest in writing stories is still very low because students usually do not have ideas so they do not understand what to explain and present in writing. Therefore, interest in writing needs to be increased starting from elementary education. This study is quantitative and aims to describe the effect of using the Comica application on the interests and writing skills of grade V students of SD Negeri 111/I Bulian. The design of this study is included in the pre-experimental type. Based on the data analysis from the discussion that has been carried out from the results of obtaining hypothesis testing using the t-test, namely with a significance level of 0.05, the t count value = 5.22 is greater than t table = 2.01. In addition, seen from the results of the post-test calculation of the experimental class using comica, it is known that the average value is 80.36 which shows a higher value compared to the control class with an average of 75.24. This increase occurred because using comica media made students more enthusiastic and more excited in the learning process. The existence of learning media such as comica will certainly make learning better and can improve student knowledge. Thus, in this study there is a significant influence between the comica application on the interest in writing stories in grade V students in social studies.